Effects of dietary serine addition to a high plant protein diet on growth performance, body composition, hepatosomatic histological structure and metabolism of taurine synthesis in juvenile turbot ( Scophthalmus maximus L.) - Guoshan Qi; Qinghui Ai; Xiaomin Jin; Ye Mu; Kangsen Mai; Muxiang Ge; Wenxiang Zhang; Hai Ren; Qinglin Wang (Journal of Fish Biology, 2026)
A feeding trial was carried out to investigate the effects of dietary serine on feeding, growth, biochemistry composition, hepatosomatic histological structure and metabolism of taurine synthesis in turbot ( Scophthalmus maximus L.) (2.0 ± 0.01 g) fed plant protein‐based diets. A fishmeal‐based control diet (DietFM) and another two isonitrogenous and isolipidic plant‐based diets containing 0.0% (DietPP) and 3.0% (DietS‐3%) serine were formulated and fed twice daily (06:30 and 18:30) to fish in triplicate groups for 9 weeks. Feed intake in fish fed DietS‐3% was notably higher than that in fish fed DietPP ( p p > 0.05). No significant difference ( p > 0.05) was found with the increase of dietary serine in final body weight, specific growth rate, weight gain rate, feed efficiency ratio, protein efficiency ratio and survival rate when a significant increase ( p p p > 0.05). A significant increase ( p p > 0.05) in fish fed DietS‐3% showed no obvious difference with those of fish fed DietPP ( p > 0.05). The cellular morphology and cell stripes in liver of fish fed diets with 3% serine inclusion were closer to that of fish fed DietFM. Considering the results, 3% serine supplementation in a high plant protein diet significantly increased feeding, mineral accumulation, body taurine content of turbot and obviously improved hepatosomatic histological structure. It is inferred that serine in a taurine‐deficient diet can probably convert to taurine to some degree in juvenile turbot, and the transformation differs with tissue distinction.